PENGENALAN PRODUK BERBASIS ISOLAT PROTEIN IKAN PADA MASYARAKAT PUTAT JAYA BARAT-SURABAYA SEBAGAI UPAYA DIVERSIFIKASI PRODUK UNTUK MENCEGAH STUNTING - Patmawati, Patmawati; Mubarak, Ahmad Shofy; Sahidu, Adriana Monica; Pramono, Heru; Amin, Muhamad Nur Ghoyatul; Triastuti, Juni; Husein, Mohamad Akmal Alwi; Putri, Monica Angelina; Ramadhan, Novelix Arditan; Rokhim, Akhmad Nur; Rohmatin, Aulia; Wulan, Novrida; Maulidia, Cici; Arum, Kartika Dwi Sekar (Universitas Mataram, 2025)
The phenomenon of stunting has caught global attention as it may disrupt children growth and development which is important for national sakes. This problem also occurred on the community of Putat Jaya Barat, Surabaya. Despite the decrease of stunting prevalence on 2022 by 21.6%, the community of Surabaya should maintain their awareness to prevent the occurrence of stunting near in the future. Therefore, in order to prevent the occurrence of stunting, it is necessary to provide community service which is related to the introductory of protein isolate-based products from fisheries commodities. Protein isolate as a functional food has concentrated protein content which may fulfil daily consumption need. This community service activity was conducted to provide participants with the knowledge of stunting phenomenon, fisheries product diversification, and the demonstration on isolate protein production method. The result of this this community service activity showed that the participants were poorly informed with the stunting information, however the participants were still able to provide their family with adequate food consumption based on the concept of “4 Sehat 5 Sempurna”. The participants were also provided with the understanding toward fisheries product diversification. The questionnaires evaluation showed that the participants need further assistance related to the application of protein isolate on fisheries products, with the nutritional information, and healthy life socialization.